2013
DOI: 10.3928/01477447-20130523-31
|View full text |Cite
|
Sign up to set email alerts
|

Reunderstanding of Garden Type I Femoral Neck Fractures by 3-dimensional Reconstruction

Abstract: Garden type I fractures include incomplete fractures and impacted fractures. With advances in scientific technology and medical treatment, certain deficiencies of the Garden classification have become apparent. The authors hypothesized that the incidence of incomplete femoral neck fractures was low and that impacted femoral neck fractures were not undisplaced and stable fractures. A new method was developed to precisely measure the spatial displacement of the femoral head in impacted femoral neck fractures. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…There is still disagreement on the existence of this type of fracture. [ 3 , 4 ] Herein, we report 2 patients with the Garden type I femoral neck fractures and confirm the real existence of it. This study was carried out in accordance with the guidelines of the Declaration of Helsinki.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…There is still disagreement on the existence of this type of fracture. [ 3 , 4 ] Herein, we report 2 patients with the Garden type I femoral neck fractures and confirm the real existence of it. This study was carried out in accordance with the guidelines of the Declaration of Helsinki.…”
Section: Introductionsupporting
confidence: 66%
“…There is still disagreement on the existence of Garden type I fractures. [ 3 , 4 ] A review from Raaymakers [ 7 ] even considered that the really nondisplaced femoral neck fracture does not exist. With the development of radiology, CT scans allow for more accurate diagnosis of the displacement of femoral neck fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is has been shown in recent work that most Garden stage I fractures-undislocated fractures per definitionare neither undislocated nor stable when studied using three-dimensional CT technology. This study especially revealed significant posterior and rotational displacement [5]. A missed or underestimated posterior and rotational displacement may result in impaired blood supply to the femoral head due to a kinking of the retinacular nutrient vessels [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent 3D-CT-based research on Garden stage 1 fractures has demonstrated that there is considerable rotational displacement in most patients. They concluded that most Garden stage 1 fractures are neither undisplaced nor stable [5]. Moreover, the preoperative radiographs of unstable fracture types should be understood as a snapshot.…”
Section: Introductionmentioning
confidence: 97%
“…Currently, no superior method existed to measure the residual displacement of the femoral head. A new method that was published in 2013 12 was developed by our team to measure the preoperative displacement of Garden stage I fractures based on 3-dimensional reconstruction software. In our study, Garden stage I femoral neck fractures were found with some degrees of displacement that was invisible in plain x-ray.…”
Section: Introductionmentioning
confidence: 99%